Gene profiling reveals association between altered Wnt signaling and loss of T‐cell potential with age in human hematopoietic stem cells. Issue 4 (30th May 2014) - Khoo, Melissa L. M.; Carlin, Stephen M.; Lutherborrow, Mark A.; Jayaswal, Vivek; Ma, David D. F.; Moore, John J.
Summary Functional decline of the hematopoietic system occurs during aging and contributes to clinical consequences, including reduced competence of adaptive immunity and increased incidence of myeloid diseases. This has been linked to aging of the hematopoietic stem cell (HSC) compartment and has implications for clinical hematopoietic cell transplantation as prolonged periods of T‐cell deficiency follow transplantation of adult mobilized peripheral blood (PB), the primary transplant source. Here, we examined the gene expression profiles of young and aged HSCs from human cord blood and adult mobilized PB, respectively, and found that Wnt signaling genes are differentially expressed between young and aged human HSCs, with less activation of Wnt signaling in aged HSCs. Utilizing the OP9‐DL1 in vitro co‐culture system to promote T‐cell development under stable Notch signaling conditions, we found that Wnt signaling activity is important for T‐lineage differentiation. Examination of Wnt signaling components and target gene activation in young and aged human HSCs during T‐lineage differentiation revealed an association between reduced Wnt signal transduction, increasing age, and impaired or delayed T‐cell differentiation. This defect in Wnt signal activation of aged HSCs appeared to occur in the early T‐progenitor cell subset derived during in vitro T‐lineage differentiation. Our results reveal that reduced Wnt signaling activity may play a role in the age‐related intrinsic defects of aged HSCs and early hematopoietic progenitors and suggest that manipulation of this pathway could contribute to the end goal of improving T‐cell generation and immune reconstitution following clinical transplantation.